The Influence of Business and Government Structures on the Autonomy of Lithuanian Online Media - Valentinavičius, Vytautas (Žurnalistikos tyrimai, 2017)
This article is aimed at presenting a complex approach to the media autonomy concept, with particular focus on the most real aspects of journalistic activity and the factors affecting them. The paper actualizes the notion of media and professional autonomy, introduces the Western tradition of journalistic culture and considers the decisions being made and how they affect professional independence in Lithuanian newsrooms. The practical research part of this piece mostly focuses on newsrooms operating online. Based on the findings of the research conducted on the relationships of business and government structures with the media, and the data of the survey of editors and journalists, it can be stated that several factors affect the autonomy of newsrooms and journalists of Lithuanian internet portals: 1) the owners of a media outlet; 2) the political and business interests of the owners; 3) an absence of ethical norms, such as documents regulating professional activities; 4) an absence of mechanisms for feedback and resolution of conflicts of interests; 5) a lack of transparency and impartiality in internet portals; 6) political and business interests; 7) the hierarchical structure of an editorial office. An analysis of the information about owners and documents published in internet portals revealed that the editorial offices either do not provide any information about the shareholders (owners) altogether or this information is provided to the general public in a laconic and sleek manner. Regardless of the fact that some of the portals provide information that shareholders do not interfere with the work of the editorial office, none of them referred to a mechanism for dissociating the editorial office from the interests of the owners (shareholders). The portals do not provide information about the mechanisms for resolving conflicts (between the readers and the newsroom) operated in the newsrooms. Moreover, there is no information on how the conflicts of editors and journalists pertaining to professional ethics are resolved. The majority of newsrooms (except for Delfi.lt) do not familiarize readers with their work culture. The survey of the journalists and editors of internet media outlets revealed that the newsrooms are not sufficiently autonomous – the majority of those surveyed do not think they work in autonomous newsrooms. The lack of autonomy of newsrooms of the internet portals was also corroborated by the fact that there are topics avoided by journalists and editors alike. Generally, they are associated with competitors, politicians or business structures, advertising customers and the interests of owners. It can be assumed, based on the corpus of the replies given by editors and journalists, that a strong hierarchical structure prevails in editorial offices influencing the individual autonomy of journalists. The overall analysis of the journalist replies shows that the journalists do not complete the texts themselves (texts are corrected; titles are changed). Although the corrections are coordinated with the journalists, the editors make the final decision concerning them. Moreover, the lack of professional autonomy of the journalists is also shown by the fact that journalists are commissioned to write articles, whereas certain articles are removed from the internet space.